Kikuchi-Fujimoto disease - Alakkad, Ashraf; Alakkad, Mohamed (International Journal of Advances in Medicine, 2021)
A lady from Sudan was referred to our medical clinic as a case of cervical lymphadenopathy with gradual enlargement. She had no complaint. The cervical lymphadenopathy was not associated with pain, fever, weight loss, cough, neither bleeding nor other associated swellings. There was no history of chronic medical problems including TB and underwent thorough investigations including LN biopsy. Lymphoma was initially suspected. Fine-needle aspiration and excision biopsy were undertaken. Histological analysis later suggested Kikuchi-Fujimoto disease, also known as histiocytic necrotizing lymphadenitis. Kikuchi-Fujimoto disease (KFD) was described in 1972 as lymphadenitis with focal proliferation of reticular cells accompanied by numerous histiocytes and extensive nuclear debris. KFD, frequently found in East Asian countries, is rare in the UK. No definite etiology of KFD is known despite autoimmune and infection factors being suggested. The diagnostic hallmark is histological findings from lymph nodes. Steroid therapy could be used in severe cases. KFD is relatively unknown and this case report aims to highlight its occurrence in our population.